2020
DOI: 10.1186/s12951-020-00641-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale perfluorocarbon expediates bone fracture healing through selectively activating osteoblastic differentiation and functions

Abstract: Background and rationale: Fracture incidence increases with ageing and other contingencies. However, the strategy of accelerating fracture repair in clinical therapeutics remain a huge challenge due to its complexity and a longlasting period. The emergence of nano-based drug delivery systems provides a highly efficient, targeted and controllable drug release at the diseased site. Thus far, fairly limited studies have been carried out using nanomedicines for the bone repair applications. Perfluorocarbon (PFC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…It can dissolve oxygen, thus playing a crucial role in the delivery of oxygen for organ preservation [ 58 ]. Recent evidence reported the bone fracture healing properties of nanoscale perfluorocarbon in a rabbit model with radial fractures, as shown by the elevations in soft callus formation, collagen synthesis, as well as the expression of VEGF, MMP-9, and OCN [ 59 ]. Perfluoro-15-crown-5-ether (PFCE) is a commonly used perfluorocarbon, which is chemically and biologically inert, temperature and storage stable, as well as posing no infectious risk.…”
Section: The Enhancement Of Cpc Using Synthetic Materialsmentioning
confidence: 99%
“…It can dissolve oxygen, thus playing a crucial role in the delivery of oxygen for organ preservation [ 58 ]. Recent evidence reported the bone fracture healing properties of nanoscale perfluorocarbon in a rabbit model with radial fractures, as shown by the elevations in soft callus formation, collagen synthesis, as well as the expression of VEGF, MMP-9, and OCN [ 59 ]. Perfluoro-15-crown-5-ether (PFCE) is a commonly used perfluorocarbon, which is chemically and biologically inert, temperature and storage stable, as well as posing no infectious risk.…”
Section: The Enhancement Of Cpc Using Synthetic Materialsmentioning
confidence: 99%
“…Consequently, PFCs promoted osteoblast differentiation and raised the levels of helpful cytokines, including vascular endothelial growth factor (VEGF) and matrix metalloproteinase 9 (MMP-9). 52 By enhancing dissolved oxygen dispersion through the matrix, systems incorporating PFCs can increase oxygenation but are not intended to serve as oxygen reservoirs. Although the improvement in effectual diffusivity is measurable, whether it reliably benefits cells remains to be determined.…”
Section: Perfluorocarbons (Pfcs)mentioning
confidence: 99%
“…Research on bone fractures in rabbits demonstrated that injection of a PFC nanoemulsion could accelerate bone regeneration under a hypoxic atmosphere by increasing the oxygen concentration at the fracture site. Consequently, PFCs promoted osteoblast differentiation and raised the levels of helpful cytokines, including vascular endothelial growth factor (VEGF) and matrix metalloproteinase 9 (MMP-9) …”
Section: Absorbed Oxygen-generating Biomaterialsmentioning
confidence: 99%
“…Treatment of irregular bone defect and comminuted fracture, due to population aging, sports injury and traffic accident, remain as common clinical challenges. Due to the accumulating needs for faster healing after operation, the clinical demand for injectable biomaterials is increasing, which can allow for regeneration of diseased/injured bone tissue with minimally-invasive strategies [ [1] , [2] , [3] , [4] ]. Currently, poly (methyl methacrylate) (PMMA) is the most commonly used injectable material for bone supporting and pain relief after osteoporosis vertebral fracture [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%